2018
DOI: 10.3390/nu10101487
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Tissue Distribution of Cyano–B12 and Hydroxo–B12 One Week after Oral Intake: An Experimental Study in Male Wistar Rats

Abstract: Foods contain natural vitamin B12 forms, such as hydroxo–B12 (HO–B12), whereas vitamin pills contain the synthetic cyano–B12 (CN–B12). Recent studies in rats showed different tissue distributions of CN–B12 and HO–B12 24 h after oral administration. Here, we investigate whether these differences are sustained or leveled out with time in both B12-deplete and -replete rats, thereby assessing if the two forms are equally good at maintaining a normal B12 status. Male Wistar rats were fed diets with low (n = 16) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…All in all, such mechanisms may shunt the excess of B12 out of its cells for mobilization to other tissues where it is most needed. In case of B12, the liver and kidneys are typical organs that dramatically change their intracellular levels depending on extracellular supply of B12 and the requirement of the cells [ 9 ]. It should be, however noted, that different forms of B12 (e.g., cyano- vs. hydroxo-B12) can give different ratios of intracellular/extracellular vitamin if administered at equal quantities [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…All in all, such mechanisms may shunt the excess of B12 out of its cells for mobilization to other tissues where it is most needed. In case of B12, the liver and kidneys are typical organs that dramatically change their intracellular levels depending on extracellular supply of B12 and the requirement of the cells [ 9 ]. It should be, however noted, that different forms of B12 (e.g., cyano- vs. hydroxo-B12) can give different ratios of intracellular/extracellular vitamin if administered at equal quantities [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In case of B12, the liver and kidneys are typical organs that dramatically change their intracellular levels depending on extracellular supply of B12 and the requirement of the cells [ 9 ]. It should be, however noted, that different forms of B12 (e.g., cyano- vs. hydroxo-B12) can give different ratios of intracellular/extracellular vitamin if administered at equal quantities [ 9 ]. Possible explanation may be that the different conversion rates of the inactive form of B12 to the active form, where the unprocessed inert B12 forms are expelled [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such an approximation (being not literally true) is sufficiently fair, because no leakage of HO/Me/AdoCbls to the medium was detected in the CNCbl setup (Section 3.4). In addition, previous human and rat studies revealed that the ratios of (endogenous tissue Cbl)/(plasma Cbl) ranged from approximately 10 to 100 ( [1,40] and refs. thereof).…”
Section: Study Limitationsmentioning
confidence: 96%